Simplify the expression (4x − 3)(x + 5).

A.
4x2 − 17x + 15
B.
4x2 + 17x + 15
C.
4x2 + 17x − 15
D.
4x2 − 17x − 15

A. 4x2 − 17x + 15

To simplify the expression (4x − 3)(x + 5), we can use the distributive property to multiply the terms:

(4x − 3)(x + 5) = 4x(x) + 4x(5) - 3(x) - 3(5)

First, let's simplify each term:

4x(x) = 4x^2
4x(5) = 20x
-3(x) = -3x
-3(5) = -15

Putting it all together, we have:

4x^2 + 20x - 3x - 15.

Combining like terms:

4x^2 + 17x - 15.

Therefore, the simplified expression is 4x^2 + 17x - 15.

The correct answer is C. 4x^2 + 17x − 15.